ANALYSIS OF COMPETITIVENESS AND THE IMPACT OF GOVERNMENT POLICIES ON DAIRY COMMODITIES IN PASURUAN DISTRICT - yulianti, Nurdiana; Muhaimin, Abdul Wahib; Maulidah, Silvana (Socio-Economics/Agribusiness Department, 2024)
Milk is a food commodity that Indonesia continues to import in large quantities and continues to increase every year. This happens because demand continues to increase and cannot be matched by domestic production. This study aims to determine the competitiveness of dairy milk in Lekkok District, Pasuruan Regency which is the area with the largest dairy cattle population in East Java through the Policy Analysis Matrix (PAM) method. The analysis shows that the PCR value is -0.54 (<1), meaning that milk cultivated by farmers has a competitive advantage. The value of DRCR is 0.02 (<1) indicating that the milk cultivated by farmers also has a comparative. Overall, the input-output policy implemented by the government has not fully benefited farmers. The results of the sensitivity analysis showed that when the rupiah exchange rate weakened at 10% and 20%, the costs incurred by farmers increased and were directly proportional to the revenues that also increased.